La incorporación de los pueblos originarios a las conmemoraciones del 2021 mexicano: peticiones de perdón y reconciliación nacional - Inmaculada Verdú Sánchez (Cahiers des Amériques Latines)
The year 2021 was commemorated as “The Year of Independence and Greatness of Mexico”. The President of the Mexican Federal Republic, Andrés Manuel López Obrador, saw the commemoration as the ideal occasion to bring Mexicans to reconcile around the nation. A necessary step towards this was for the Mexican state to apologise for the historical wrongs committed against the native peoples, as well as to recognise the valuable contribution they have made to Mexican history. To this end, the federal government scheduled two reparation ceremonies as part of the 2021 commemorative programme. However, not all members of the country's native communities responded positively to the government's initiative, with some considering the president's apology insufficient.